Grito do silêncio: axiologia dos pedidos de desagravo na Comissão de Direitos e Prerrogativas da OAB/SP - Boneli, Daniela Tamaio Lopes (2020)
The present study aims to identify the degree of understanding by lawyers, the institute of the displeasure provided for in the Statute of the OAB, in the face of the constant requests for injuries referred to the OAB - Section São Paulo, when many questions related to the offense to the Rights and Prerogatives of Lawyers do not fall within the legal hypothesis of injury. This study is justified because there is an immense disparity between the admissibility opinion that attests to the existence of an offense to the rights and prerogatives of lawyers and what is really a case of injury. The bibliographic research method allowed collecting data from the decisions of the Prerogative council of the OAB/SP in 2018, referring to the theme public disity and as a result it was found that every case of displeasure is a hypothesis of offense to prerogatives, but not every case of offense to the prerogatives triggers public disinjury, although erroneously perceived as synonyms by some offended. Legal axiology allows identifying these convergent and supplementary values, although considered as a public act, occurs between four walls of the subsections without effective repercussion